2014
DOI: 10.1371/journal.pone.0099405
|View full text |Cite
|
Sign up to set email alerts
|

Sialidase NEU3 Dynamically Associates to Different Membrane Domains Specifically Modifying Their Ganglioside Pattern and Triggering Akt Phosphorylation

Abstract: Lipid rafts are known to regulate several membrane functions such as signaling, trafficking and cellular adhesion. The local enrichment in sphingolipids and cholesterol together with the low protein content allows their separation by density gradient flotation after extraction with non-ionic detergent at low temperature. These structures are also referred to as detergent resistant membranes (DRM). Among sphingolipids, gangliosides play important roles in different biological events, including signal transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…Moreover, the ability of oleate alone to enhance insulin sensitivity in L6 myotubes concurred with increased NEU3 protein. Together, these findings support a positive role for NEU3 sialidase in facilitating insulin signal transduction, potentially through its reported ability to co‐localise with caveolin proteins in membrane microdomains[54,55].…”
Section: The Role Of Gm3 In Obesity‐induced Insulin Resistancesupporting
confidence: 56%
“…Moreover, the ability of oleate alone to enhance insulin sensitivity in L6 myotubes concurred with increased NEU3 protein. Together, these findings support a positive role for NEU3 sialidase in facilitating insulin signal transduction, potentially through its reported ability to co‐localise with caveolin proteins in membrane microdomains[54,55].…”
Section: The Role Of Gm3 In Obesity‐induced Insulin Resistancesupporting
confidence: 56%
“…However, it has been demonstrated that they are also present in the endosomal compartment, in the phagosomes, in the Golgi, and in the exosomes (33)(34)(35)(36). Previously, we demonstrated that NEU3 participates in a complex cell trafficking between the endosomes and the membrane, and, as it reaches the plasma membrane, it is initially associated with non-detergent-resistant membrane areas, but eventually it partially translocates to detergent-resistant membranes, reaching an even distribution (4). Therefore, the interaction with Flotillin1 could be instrumental for the mobilization of NEU3 in the cell membrane.…”
Section: Neu3 Sialidase Protein Interactorsmentioning
confidence: 85%
“…It is topologically associated with the outer leaflet of the plasma membrane, where its natural gangliosidic substrates are present (2). The localization of NEU3 on the plasma membrane has been recently defined to be dynamic, because the enzyme is distributed between detergent-resistant membranes and nondetergent-resistant membranes, in a cholesterol-dependent manner, suggesting its presence in supramolecular organized structures (2,4). Moreover, NEU3 could be found also in vesicular structures corresponding to the endosomes (2).…”
mentioning
confidence: 99%
“…Units/ml Penicillin, 100 mg/ml Streptomycin and 10% (v/v) Fetal Bovine Serum (FBS) (GIBCO). Cells were stably transfected with pcDNA3.1-mNEU3eHA [13], while Mock cells were obtained by transfection with pcDNA3.1 empty vector. Transfectants were grown in complete medium supplemented with 0.5 mg/ml G418.…”
Section: Cell Culture Transfection and Treatmentsmentioning
confidence: 99%
“…Up-regulation of NEU3 has been correlated to different human tumors such as colon, renal, prostate and ovarian cancers [12]. Overexpression of NEU3 in HeLa cells induces the phosphorylation of Akt even in the absence EGF [13] and a recent study has demonstrated that NEU3 can also directly act on EGFR glycan(s), resulting in the activation of the receptor [14]. In the last few years many scientific papers demonstrated the involvement of the enzyme in oncogenic transformation mediated by EGFR [10,15].…”
Section: Introductionmentioning
confidence: 99%